PELATIHAN PENGOLAHAN LIMBAH SALAK MENJADI TEH DAN KOPI DI DESA ARGOYUWONO KABUPATEN MALANG - Cholishah, Naila; Firmansyah, Mohammad Akbar Hafidz; Nafilah, Dilla Amalia Hamdi; Fauzan, Slamet (Universitas Negeri Malang, 2023)
Salak as a local commodity in Argoyuwono Village is usually directly sold or consumed by the community. Selling salak directly to collectors has low economic value and consumption of salak produces piles of salak waste. Waste bark and seeds contain antioxidants that are beneficial to health, so they have the potential to be processed into products. Service activities through training in making salak bark tea and salak coffee beans are carried out using the methods of 1) survey and observation, 2) analysis of problems and needs, 3) compiling procedures, 4) product manufacture, 5) packaging design, 6) preparation of cost of goods sold, 7) output products, 8) training, 9) evaluation and monitoring. Processing salak bark into tea and salak seeds into coffee in the Argoyuwono Village community can increase community innovation so that they are able to carry out the production of salak seed coffee and salak bark tea. The resulting product can increase the economic value and reduce the pile of salak waste.